THE EFFECT OF USING KAHOOT IN WRITING FUNCTIONAL TEXT FOR SENIOR HIGH SCHOOL STUDENTS - Elvyra Elvyra; Theodesia Lady Pratiwi (FKIP, Universitas Palangka Raya, 2023)
Based on the observation at a private senior high school in Batam, the students were not fully engaged with the class. Some of them were busy with their activity, resulting in not paying attention in class. The teaching media was boring too. Thus, the authors implemented Kahoot as game-based learning media to engage students in the class as well as to improve the students’ writing skills in functional text. Classroom Action Research (CAR) method was implemented in the study. Thirty-eight students from class X-10 from a private senior high school in Batam participated in this study. A pre-test, post-test, and rubric scores were used to evaluate the student’s writing skills in functional text. The authors also shared the questionnaire with the students to measure their engagement after the implementation. After the Kahoot implementation, the students’ writing has notably gotten better, which has improved from 65,30 (pre-test) to 72,48 (post-test in cycle 1) and 88,82 (post-test in cycle 2). Equally, the students showed a positive attitude toward their engagement in class, whether in affective, behavioural, or cognitive engagement.